2017
DOI: 10.1107/s2053273317002297
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse single-crystal scattering corrected for molecular form factor effects

Abstract: This paper shows that chemical short-range order in two-component molecular crystals can be solved directly by separating the influence of the molecular form factor from the diffraction pattern. This novel technique is demonstrated by analysing the diffuse scattering of tris-tert-butyl-1,3,5-benzene tricarboxamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Atom This molecule has been used previously by a few members of the diffuse scattering community to test their analysis methods [12,13]. The data used here were kindly provided by Arkadiy Simonov, in the form of pre-processed hkx planes [13].…”
Section: Tris-tert-butyl-135-benzene Tricarboxamidementioning
confidence: 99%
See 1 more Smart Citation
“…Atom This molecule has been used previously by a few members of the diffuse scattering community to test their analysis methods [12,13]. The data used here were kindly provided by Arkadiy Simonov, in the form of pre-processed hkx planes [13].…”
Section: Tris-tert-butyl-135-benzene Tricarboxamidementioning
confidence: 99%
“…1 illustrates this factorization. Schmidt & Neder (2017) showed that, in such systems, I SRO can be obtained by dividing the diffuse scattering by the known form factor difference squared, or, in the case where this is not known, by dividing by an average form factor squared. The resulting function can be projected into one reciprocal-space unit cell, and the Warren-Cowley SRO parameters (Warren et al, 1951) can be extracted directly from it through a least-squares refinement, providing a quantitative description of local correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative refinement of the 2D-ÁPDF is possible using the YELL code (Simonov et al, 2014b). We used a suitably customized version (Schmidt & Neder, 2017) to refine WC correlation parameters for nearest neighbours; by exploiting various symmetry relations there are just three independent parameters to be determined (full details are given in the supporting information). These parameters effectively define the probabilities of different tile pairs, and our results correspond to a better-than- RMC -but not yet perfect -observation of the original matching rules: the rules are obeyed 87.6 (5)% and 76.8 (57)% of the time for correlations extracted from neutron and X-ray data, respectively.…”
Section: 13mentioning
confidence: 99%
“…Quantitative refinement of the 2D-∆PDF is possible using the YELL code 45 . We used a suitably customised version 46 to refine Warren-Cowley correlation parameters for nearest-neighbours; by exploiting various symmetry relations there are just three independent parameters to be determined (full details are given in the supplementary information). These parameters effectively define the probability of different tile-pairs, and our results correspond to a better-than-RMC -but not yet perfect -observation of the original matching rules: these rules being obeyed 87.6(5)% and 76.8(57)% of the time for neutron and X-ray data, respectively.…”
Section: Comparison With Established Refinement Approachesmentioning
confidence: 99%